Replenishment of Cultivated Soybean Varietes Market (Glycine hispida Maxim, Moench.. - О. І. Безручко; О. В. Колесніченко (Plant Varieties Studying and Protection)
There provided ways of using valuable protein crop, soybean, as well as its production worldwide growth rates during recent years, possibility and necessity of attaching to the crop a strategic importance in our State and the tasks and outlooks of soybeanrecourses generation. A complete description of new soybean varieties listed in the Register of Varieties Suitable for Dissemination in Ukraine has also been provided.